Lambeth Walk, czyli widz wyzwolony spod presji obrazu - MAREK HENDRYKOWSKI (Images)
The Lambeth Walk, or the spectator liberated from the pressure of the picture A quintessential work of British and European cinema of World War II “The Lambeth Walk” is the epitome of world-class art of moving picture editing. Marek Hendrykowskis close-reading analysis places this short movie in its aesthetic, cultural and generic contexts and in the international landscape of the anti-propaganda film.